Community Economic Empowerment Through Prosperous Village-Owned Enterprises (BUMdes) in Pajinian Village, West Adonara District, East Flores Regency - Nikolaus Narek Kopong (LPPM Institut Studi Islam Sunan Doe, 2024)
Village-Owned Enterprises (BUMDes), is an economic entity in which both part and majority of the capital owned is controlled by the village government through direct participation taken from the separated village treasury, with the aim of managing inventory, services, and other business activities with the aim of increasing welfare. as many rural residents as possible. Community Economic Empowerment is expected to be able to take advantage of all potential economic resources, economic institutions, and the potential for villages with natural and human resources is no exception. This study aims to analyze Community Empowerment activities in Pajinian Village, West Adonara District, District East Flores, East Nusa Tenggara Province. The study used a qualitative method accompanied by interview techniques and direct questions and answers with the subjects studied, namely: the head of the Pajinian village, the head of the Bumdes of Pajinian village, the management of the Pajinian village of Bumdes, members of the Pajinian village community. There is a relationship between Community Empowerment and the formation of BUMDES in Pajinian Village, West Adonara District.